Maternal age and the rising incidence of hypertensive disorders of pregnancy: A comprehensive analysis of national claims data from Japan. - Naomi Maeda; Masayuki Koyama; Shintaro Takatsuka; Keisuke Oyatani; Nobuaki Himuro; Tasuku Mariya; Yoshika Kuno; Shiro Hinotsu; Tsuyoshi Saito; Hirofumi Ohnishi (PLoS ONE)
Background Hypertensive disorders of pregnancy (HDP) significantly increase the risk of developing hypertension and cardiovascular disease (CVD) later in life and are a major cause of maternal mortality. However, little is known about the nationwide, long-term, all-inclusive status of HDP. Objective To estimate the incidence of HDP from 2011 to 2019 in Hokkaido, Japan, with a focus on age groups. Methods Using National Database (NDB) insurance medical data, a retrospective analysis was conducted. Due to the absence of direct pregnancy data, birth numbers were used as a surrogate for the number of pregnant women to calculate the incidence of HDP. Results The average incidence rate of HDP over 9 years was 6.37%. The incidence rate was lowest among women aged 25-29 years, at 5.58% (95% confidence interval [CI]: 5.43-5.73), and increased with age, peaking at 10.58% (95% CI: 10.10-11.09) among women over 40 years. Notably, the incidence rate for women under 20 years of age was 6.70% (95% CI: 5.97-7.51), which was higher than that for women in their 20s. A mean annual increase of 0.25% in age-adjusted incidence was observed during this period, which was statistically significant (R² =  0.87, p <  0.01). Conclusion This study reveals that the risk of developing HDP is associated with both older childbearing and younger pregnancies and follows a J-curve, suggesting that factors other than maternal aging also contribute to the increased incidence of HDP and that further research on risk factors for HDP, which is on the rise worldwide, is urgently needed.